Investasi Valuta Asing dan Penerapannya Menggunakan Software Metatrader: Sebuah Alternatif - Yoyo Cahyadi (Bina Nusantara University, 2013)
Investment in foreign exchange is growing very fast recently because of liberal market system and technology advancement. Technology makes investment in foreign exchange can be performed easier, faster, and simple regarding the foreign exchange market open 24 hours in working days. In fact, there are just a few people who understand foreign exchange investment and how to use the tool needed in this kind of investment. The purpose of this paper is to give a description on how to use foreign exchange as an investment and using MetaTrader 5 software as a tool of it. Its features support foreign exchange market which often moves very fast. Understanding of foreign exchange market and software operation are the first step to start the investment.